PEMBUATAN DEMPLOT SISTEM PEMANAS KADANG INDUKAN DENGAN MEMANFAATKAN ENERGI PANAS TERBUANG DARI INKUBATOR PENETAS TELUR PUYUH: indonesia - Irna Sari Maulani; Heris Syamsuri (Universitas Majalengka, 2022)
Eggs and quail meat are in great demand by the public because they have high nutritional value and affordable prices. Consumption of eggs and quail in Ciamis Regency continues to increase. increased consumption should be followed by egg and quail production. To meet these needs, it is necessary to manufacture a quail egg incubator (incubator) so that the egg hatching process is relatively easier and more practical with better hatching results. This service aims to provide training for the manufacture of demonstration plots for the heating system of the quail broodstock cage by utilizing the wasted heat from the incubator. In addition, it can also provide training and skills for making quail egg incubators with a capacity of 50 eggs so that hatching eggs is relatively easier and more practical with better hatching results. The service activity was carried out by providing counseling about raising quail eggs, then continued by providing training and skills in making an egg incubator (incubator) then the next stage providing skills in making demonstration plots of the heating system for quail egg brooders by utilizing the wasted heat from the incubator. The results of the service that have been carried out are as follows quail farmers in Sandingtaman Village have skills in making egg incubators (incubators) and making quail egg cages by utilizing wasted heat from the incubator. The results of the activity of one quail egg incubator that can be used by farmers